Events Associated With Changes in Reliance on the Veterans Health Administration Among Medicare-eligible Veterans. Issue 8 (August 2020) - Hebert, Paul L.; Wong, Edwin S.; Reddy, Ashok; Batten, Adam; Gunnink, Eric; Wagner, Todd H.; Liu, Chuan-Fen
Abstract : Objectives: We can learn something about how Veterans value the Veterans Health Administration (VHA) versus community providers by observing Veterans' choices between VHA and Medicare providers after they turn 65. For a cohort of Veterans who were newly age-eligible for Medicare, we estimated the change in VHA reliance (VHA outpatient visits divided by total VHA and Medicare visits) associated with specific events: receiving a life-threatening diagnosis, having a Medicare-paid hospitalization, or moving further from the VHA. Research Design: A longitudinal cohort study of VHA and Medicare administrative data. Subjects: A total of 5932 VHA users who completed a health survey in 1999 and became age-eligible for Medicare from 1998 to 2000 were followed through 2016. Principal Findings: More Veterans chose to rely on the VHA than Medicare (64% vs. 36.%). For a VHA-reliant Veteran, a Medicare-paid hospital stay was associated with a decrease of 7.8 percentage points (pps) ( P <0.001) in VHA reliance in the subsequent 12 months, but by 36 months reliance increased to near prehospitalization levels (−1.5 pps; P =0.138). Moving further from the VHA, or receiving a diagnosis of cancer, heart failure, or renal failure had no significant association with subsequent VHA reliance; however, a diagnosis of dementia was associated with a decrease in VHA reliance (−8.6 pps; P =0.026). Conclusions: A significant majority of newly Medicare-eligible VHA users voted with their feet in favor of sustaining the VHA as a provider of comprehensive medical care for Veterans. These VHA-reliant Veterans maintained their reliance even after receiving a life-threatening diagnosis, and after experiencing Medicare-provided hospital care. Abstract : Supplemental Digital Content is available in the text.